PENGARUH TRUEVIEW ADS YOUTUBE TERHADAP SIKAP KONSUMEN DAN DAMPAKNYA TERHADAP NIAT BELI PRODUK UNIQLO - Yolanda, Valent; Anggawidjaja, Agus Hasan Pura (Parahyangan Management Science and Practices Student Review, 2024)
Technological advances and the rapidly increasing internet use are currently good opportunities for companies. Social media and online platforms, including YouTube, can be used to advertise brands. YouTube offers a trueview ads feature (ads that appear or are displayed when a YouTube user watches a video). With YouTube trueview ads, companies are required to be able to create attractive advertisements so that viewers do not choose the "skip ads" option. The hope is that the existence of attractive advertisements can create positive consumer attitudes toward the brand being advertised, thereby generating purchase intentions from viewers of the advertisement. One company that uses trueview ads is Uniqlo. This research aims to determine the effect of Uniqlo trueview ads on consumer attitudes and their impact on Uniqlo purchase intentions. This research used purposive sampling in sample collection and collected 100 respondents with age criteria of 18 - 35 years who had seen Uniqlo's trueview ads. The data obtained was then processed using Partial Least Squares Structural Equation Modeling (PLS-SEM). From the research results, it was found that Uniqlo's trueview ads on YouTube had a positive and significant influence on purchase intentions and consumer attitudes as intervening variables.